(untitled) - Seliger, Herbert W; Shohamy, Elana Goldberg (Oxford, 2015)
Includes bibliographical references (p. 261-266) and index; This book is a clear, comprehensive guide to research methods in second language use and bilingualism; First published 1989
Keywords: Language and languages -- Study and teaching -- Research; Second language acquisition -- Research; Ngôn ngữ và ngôn ngữ học -- Dạy và học -- Nghiên cứu; Bilingualism -- Research; Song ngữ -- Nghiên cứu; Tiếp nhận ngôn ngữ thứ hai